Foam Characteristics and Sensory Analysis of Arabica Coffee, Extracted by Espresso Capsule and Moka Methods - Giovanna Lomolino; Valentina Dal Zotto; Stefania Zannoni; Alberto De Iseppi (Beverages, 2022)
The coffee extraction methods modify the structure of the foam (when it is present) and the sensory profile of the beverage. In this research, three ways of extracting and two varieties of 100% Arabica were compared. Nineteen bars and fifteen bars were applied to the coffee thanks to the use of compatible capsules and machines. The method with the moka was considered, which acts at low pressures and does not allow the formation of foam (crema). In addition, the Brazil and Guatemala Arabica varieties were considered to understand the extent to which Arabica coffee can respond in structural and sensorial terms to the extraction techniques applied. The results show that 19-bar espresso coffees have a very stable crema with very small bubbles, which give a uniform and fine structure to the coffee crema. On the contrary, the pressure at 15 bars generates more unstable foams and bubbles that tend to be disproportionate, with more marked effects in the Brazil variety. The sensory profiles of the coffees respond to the extraction techniques applied. While the coffee extracted with the moka has sensory descriptors with rather low values, those obtained at 19 and 15 bars have much wider profiles. In conclusion, different pressure intensities to the coffee extraction affect the quality of crema and the solubilization of organoleptically active compounds.